Room-temperature curable carbon cathode for hole-conductor free perovskite solar cells. (15th July 2019) - Dileep, Reshma; Kesavan, Ganesh; Reddy, Vijendar; Rajbhar, Manoj Kumar; Shanmugasundaram, Sakthivel; Ramasamy, Easwaramoorthi; Veerappan, Ganapathy
Graphical abstract: Highlights: Developed room-temperature curable carbon electrodes with high conductivity (49.5 s/cm) and low sheet resistance (4.5 Ω/□). Two-step perovskite sensitization method, with single cation was utilized. Ambient processed room-temperature curable carbon electrodes for HTM-free PSC. Devices made with the carbon PSC exhibited power conversion efficiency of 9.0% and exhibited good stability. Abstract: Hole conductor and metal cathode free perovskite solar cells (PSC) were fabricated with room temperature curable carbon as the top electrode. Conductivity and sheet resistance was optimized by varying the graphite and carbon black content. Highly conductive (49.5 s/cm), low sheet resistance (4.5 Ω/□) and porous carbon electrodes (45–50 µm) were obtained by room temperature (36 ± 1 °C) curing, while most of the reported literature uses high temperature process (400 °C). Perovskite sensitization was done in ambient conditions (36 ± 1 °C, 35% humidity) by two step method which consists of spin coating and dip coating for 10 min. XRD results confirm the complete conversion of PbI2 into MAPbI3 (perovskite) throughout the carbon layer and the layers beneath it. Conventional PSC and hole transport material (HTM) free PSC were also fabricated in the similar conditions to serve as reference devices for the carbon-based PSC. Carbon-based HTM -free PSC exhibited a power conversion efficiency (PCE) of 9.0% with a current density of 21.4 mA/cm 2 and open circuit voltage of 0.98 V. Simultaneously, PSC with conventional device architecture and HTM-free devices exhibited a PCE of 9.8% and 5.3%, respectively. A comparative study on charge transport properties and electron life time for all the three PSCs were carried out by electrochemical impedance spectroscopy (EIS) and found to be greater for carbon-based PSC. Steady-state photocurrent measurement under standard test conditions (AM 1.5G) were carried out for conventional and carbon-based PSC, and better stability and lower rate of degradation was observed for carbon-based PSC.